DESIGNING IT GOVERNANCE USING COBIT 2019 AT PT UNICHARM INDONESIA - Taliwongso, Indrajit; Mambu, Joe Yuan; Putra, Edson Yahuda; Waworundeng, Jacquline (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Information technology provides development for companies, with information technology facilitating companies in the work process, starting from managing existing information at the company to employee performance. Therefore, information technology has a good impact on companies. With the existence of information technology, IT Governance is needed to align IT and business in a company, this is done so that work processes in the company run more effectively both for employees and for corporate governance, corporate governance must be managed as well as possible so that it is organized and provides a good impact on the company, for this governance a system called COBIT is needed, because COBIT can manage everything from IT needs and business needs to corporate governance. With COBIT in a company, there will be designs that are in accordance with the wishes of the company and can be controlled more by IT management.